Analisis keuntungan nelayan purse seine yang menggunakan kapal di bawah 30 GT (studi kasus PPS Kota Kendari) - Mubaraq, Fitrah; Lawelle, Sjamsu Alam; Piliana, Wa Ode; Arami, Hasnia; Sidiq, Azwar (Jurnal Sosial Ekonomi Perikanan, 2024)
The research was conduted with the aim of determing the costs, revenues and profits obtained by small-scale purse seine fishermen (<30 GT) based PPS Kendari, Southeast Sulawesi. This research was conducted from September to November 2019. The study used a purposive sampling method by selecting 10 purse seine fishermen as respondens from a populations of 15 fishermen. Data obtained through interviews based on a questionnaire. The data collected includes age, education level, fishing experience, production and selling price. Average rspondents age in this study was 38 years old with a junior high school education level 6 years of fishing experience. This research showed that the total average monthly cost of purse seine fisheries was IDR74,629,401 and the average revenue was IDR98,800,000. This, the average monthly profit of purse seine fisheries was IDR24,170,599. This study show that of small-scale purse seine fishermen was sufficient and maybe influenced by the age, level of education fishing experience.